Digital labour and development: impacts of global digital labour platforms and the gig economy on worker livelihoods - Graham, M; Hjorth, I; Lehdonvirta, V (SAGE Publications, 2017)
Work has historically been geographically bounded. Workers and the work that they performed were inexorably linked, with labor being the most place-bound of all factors of production (Hudson, 2001). As Harvey (1989, p. 19) famously noted, workers are unavoidably place-based because “labor-power has to go home every night.” But the widespread use of the Internet has changed much of that. Clients, bosses, workers, and users of the end products of work can all be located in different corners of the planet. This paper is about what the spatial unfixing of work means for workers in some of the world’s economic margins. It provides examples illustrating who it is that performs much of the digital work that is carried out today, and reflects on some of the key benefits and costs associated with these new digital regimes of work.